Introducere: aspecte privind dezvoltarea spațiului mediatic online și rolul său în perioada pandemiei, cu accent pe social media - Simu, Mona; Bălășescu, Mădălina (Calitatea Vieții, 2022)
The article shortly presents the emergence and development of Online Media, with an accent on the description and analysis of Social Media and on the context regarding media in the moment of Covid 19 pandemic outbreak. It also introduces the two articles which are part of the Special Section dedicated to Social Media and its role during pandemic times.